A neutrophil signature is strongly associated with increased cardiovascular risk in gout. (14th November 2020) - Vedder, Daisy; Gerritsen, Martijn; Nurmohamed, Michael T; van Vollenhoven, Ronald F; Lood, Christian
Abstract: Objective: To investigate the association between neutrophil activation and cardiovascular risk in gout patients. We hypothesize that neutrophil activation mediates inflammation and therefore takes part in atherogenesis in gout patients. Method: Patient data were collected from 75 consecutive gout patients participating in the Reade gout cohort Amsterdam. Levels of neutrophil extracellular traps (NETs) and neutrophil activation (calprotectin and peroxidase activity) were analysed by ELISA and fluorimetry in plasma and compared with healthy controls. Markers of neutrophil activation were related to clinical markers of cardiovascular risk, including BMI, smoking, blood pressure, lipid profile and 10 year risk of cardiovascular mortality (EU-SCORE). Results: Increased levels of NETs were found in gout patients, although increased levels were not associated with cardiovascular risk. However, markers of neutrophil activation, including peroxidase activity correlated with waist:hip ratio (β = 0.33, P  < 0.001), cholesterol ratio (β = 0.46, P  < 0.005) and triglycerides (β = 0.60, P  < 0.001) as well as the 10 year risk of cardiovascular mortality (β = 0.44, P  = 0.001). Calprotectin levels were elevated in hypertension ( P  = 0.005) and diabetes ( P  = 0.02). Finally, gout patients with high levels of both peroxidase and calprotectin ('neutrophil activation signature') had a markedly elevated cardiovascular risk score ( P  = 0.001), with 68% of the patients having high cardiovascular risk (odds ratio 2.9, P  = 0.03). Conclusion: We demonstrated elevated levels of neutrophil activation markers, MPO and calprotectin in gout patients as compared with healthy controls. Of note, neutrophil activation markers were associated with several risk factors for cardiovascular disease, including hyperlipidaemia, hypertension and diabetes. Finally, the presence of a neutrophil activation signature was strongly associated with an increased 10 year risk of cardiovascular mortality. Further studies are needed to determine whether gout-specific factors and/or cardiovascular risk factors contribute to the elevated neutrophil activation observed in these patients.